Study protocol using informatics to identify and recruit a cohort of older adults in Florida to develop teleneuropsychological norms - Glenn Smith; Ambar Perez-Lao; Gelan Ying; Ellie Mitova; Amanda Morales; David Marra; Franchesca Arias; Shellie-Anne Levy (BMJ Open)
Introduction The use of teleneuropsychology or neuropsychological remote assessment increased during and after the COVID-19 pandemic in 2020. Teleneuropsychology facilitates remote assessment for populations that do not have access to neuropsychological services as well as individuals who are vulnerable or have physical restrictions that would otherwise make it difficult for individuals to receive appropriate care. However, there are many instruments that are not validated or lack normative data for the overall population. Therefore, this study aims to develop normative data for a neuropsychological battery administered on telehealth with commonly used tools to identify cognitive performance in older adults.Methods and analysis The following study will use a previously informatics-generated list of participants who have a lower risk of developing Alzheimer’s disease and other related dementias. Participants will complete screening surveys related to cognitive and health status. They will also complete questionnaires related to sociodemographic information, depression, functionality and social determinants of health. Participants will undergo a teleneuropsychological battery examination via remote assessment. We estimate recruiting 500 participants to establish normative data.Ethics and dissemination The current protocol is approved by the University of Florida’s Institutional Review Board. Results will be analysed and disseminated in a research paper once sample number goals are completed.